Effect of traverse speed on abrasive waterjet machining of Ti-6Al-4V alloy - Hascalik, Ahmet; Caydas, Ulas; Gurun, Hakan (Elsevier Sci Ltd, 2007)
In the presented study, Ti-6A1-4V alloy, known as one of the difficult-to-machine materials using conventional machining processes, was machined under varying traverse speeds of 60, 80, 120, 150, 200, and 250 mm/min by abrasive waterjet (AWJ) machining. After machining, the profiles of machined surfaces, kerf geometries and microstructural features of the machined surfaces were examined using surface profilometry and scanning electron microscopy (SEM). The experimental results indicate that the traverse speed of the jet is a significant parameter on the surface morphology, and the widths and features of different regions formed in the cutting surface change according to the traverse speed. It was also observed that the kerf taper ratio and surface roughness increase with increasing traverse speed in chosen conditions. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: AWJM; jet traverse speed; Ti-6Al-4V